Alcoholism Treatment in the United States: An Overview - Fuller, Richard K. (Alcohol Res Health, 1999)
On any given day, more than 700,000 people in the United States receive alcoholism treatment in either inpatient or outpatient settings. For many of those patients, detoxification—with or without pharmacotherapy—is the first step of treatment. The major behavioral approaches currently used in alcoholism treatment include cognitive-behavioral therapy, motivational enhancement therapy, and Alcoholics Anonymous (AA) or related 12-step programs. Clinical studies, such as the Project MATCH trial, have compared the effectiveness of these approaches. Overall, that study detected no significant differences among the three treatments in patient outcome, although certain treatment methodologies may be most appropriate for patients with certain characteristics. Pharmacotherapy with aversive or anticraving medications may supplement behavioral treatment approaches. Brief interventions that are delivered by primary health care providers also have been shown to reduce drinking levels, particularly in nondependent drinkers.